Bronchus-like Structures in Ovarian Teratomas: Report of a Series of a Previously Unreported Phenomenon With Potential For Misdiagnosis. (March 2022) - Rajendran, Simon; Boyd, Clinton; Shah, Rajeev; Stewart, Colin J.R.; McCluggage, W. Glenn
Abstract : We report 10 cases of a previously undescribed lesion within ovarian teratomas which we designate bronchus-like structures. The lesions occurred in patients aged 16 to 56 yr (mean: 36) and involved the left ovary (n=5) or right ovary (n=5). Nine cases were mature teratomas (dermoid cysts/mature cystic teratomas or mature solid teratomas), 1 with somatic malignant transformation, and 1 was an immature teratoma. The bronchus-like structures ranged in size from 2.5 to 10 mm and were unifocal (7 cases) or multifocal (3 cases). The morphology was relatively constant in all cases and characterised by a well-formed bronchus surrounded by glandular structures, some of which were dilated, separated by stroma containing a variable amount of smooth muscle. In all but 1 case, a proportion of the glands contained abundant foamy cytoplasm. There was little or no nuclear atypia or mitotic activity. At low-power, the glands often had a somewhat "infiltrative" appearance and one case was originally diagnosed as a "pulmonary-type" adenocarcinoma arising in a dermoid cyst. In all cases, there was diffuse staining of the bronchus and glands with TTF1 and Napsin A, confirming the cell lineage. Follow-up in 4 cases (18–130 mo; median: 64 mo) showed no evidence of recurrence; 1 patient died from an unrelated malignancy. In reporting this apparently rare but possibly underrecognized benign lesion arising within ovarian teratomas, we discuss the differential diagnosis and stress that pathologists should be aware of this phenomenon in order to avoid an erroneous diagnosis of malignancy.